Deposition on holm oak leaf surfaces of accidentally released radionuclides - Rauret, G.; Llauradó, M.; Tent, J.; Rigol, A.; Alegre, L. H.; Utrillas, M. J. (Science of The Total Environment, 1994)
The retention of aerosols by canopies of holm oak trees in a typical Mediterranean forest is studied. Firstly, dry deposition is measured both under and outside the canopy during several months. No clear differences are observed either in the amount or in the chemical composition of the particles collected under and outside the canopy. Secondly, the leaf morphology and anatomy as well as the aerosol deposited onto the leaf surfaces are studied by scanning electron microscopy. Cuticle thickness is measured and differences are observed between young and old leaves. The distribution of aerosol particles over leaf surface is also established. Finally, the possible incorporation into leaves of a radioactive aerosol released in an accidental situation is studied, by means of a sequential extraction procedure using water and an organic solvent. From the results it can be deduced that neither the abiotic layer nor the cuticle play any important role in the retention of caesium. The studied radionuclides are mainly found in particulate form, soluble in water, or incorporated into leaves.
Keywords: Cuticle thickness; Holm oak; Leaf surface; Radionuclide deposition; Radionuclide incorporation; Sequential extraction